2014
DOI: 10.1152/jn.00578.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis of depolarization block mediated by slow inactivation of fast sodium channels in midbrain dopamine neurons

Abstract: ES, Canavier CC. Mathematical analysis of depolarization block mediated by slow inactivation of fast sodium channels in midbrain dopamine neurons. J Neurophysiol 112: 2779 -2790, 2014. First published September 3, 2014 doi:10.1152/jn.00578.2014.-Dopamine neurons in freely moving rats often fire behaviorally relevant high-frequency bursts, but depolarization block limits the maximum steady firing rate of dopamine neurons in vitro to ϳ10 Hz. Using a reduced model that faithfully reproduces the sodium current me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 58 publications
3
34
0
Order By: Relevance
“…This is consistent with the previous modeling studies showing that NMDA can elicit bursting [5658] or burst envelope [59], while AMPA abolishes high frequency firing. The dynamical explanation is that AMPAR activation shifts the minimum of the voltage nullcline across the Ca 2+ nullcline, so that for high AMPAR conductance values (as well as positive applied currents), voltage oscillations decrease in amplitude and depolarization block occurs (S3B Fig).…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with the previous modeling studies showing that NMDA can elicit bursting [5658] or burst envelope [59], while AMPA abolishes high frequency firing. The dynamical explanation is that AMPAR activation shifts the minimum of the voltage nullcline across the Ca 2+ nullcline, so that for high AMPAR conductance values (as well as positive applied currents), voltage oscillations decrease in amplitude and depolarization block occurs (S3B Fig).…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with the previous modeling studies showing that NMDA can elicit bursting [56][57][58] or burst envelope [59], while AMPA abolishes high frequency firing. The dynamical explanation is that AMPAR activation shifts the minimum of the voltage nullcline across the Ca 2+ nullcline, so that for high AMPAR conductance values (as well as positive applied currents), voltage oscillations decrease in amplitude and depolarization block occurs ( S3B Fig). Thus, DA neuron firing does not exceed the frequency of~10 Hz when driven with AMPAR activation, similarly to the experimental results (see e.g.…”
Section: Changes In the Type Of Excitability Caused By Synaptic Inputssupporting
confidence: 93%
“…The effect of co-activation of AMPA and NMDA receptors on DA neurons has been investigated in previous modeling studies where synergistic increases in firing were observed [37]. In addition, [47] show that tonic activation of NMDA receptor delays entry into depolarization block, whereas AMPA does not. Our models shows exactly the same properties and predicts synergistic effect of these receptors on the frequency growth.…”
Section: Discussionmentioning
confidence: 99%